Kemampuan Membaca Memahami Teks Deskriptif Bahasa Arab Siswa Kelas X SMK It Ibnul Qayyim Makassar - Nahra Salsabila; Nurming Saleh; Fauziah Bachtiar (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
This study employed a quantitative descriptive research design. It aimed to determine the ability of tenth-grade students at SMK IT Ibnul Qayyim Makassar to comprehend Arabic descriptive texts, as well as the factors influencing this ability. The population and sample of the study consisted of 30 students, selected using a total sampling technique. Data were collected through a reading comprehension test on Arabic descriptive texts and a questionnaire. The obtained data were then analyzed using percentage analysis techniques. The results of the study indicate that the students’ ability to comprehend Arabic descriptive texts falls into the very good category, with a percentage of 90.4%. Supporting factors include students’ interest and motivation, concentration during learning, frequent assistance from peers, family support, teaching methods that facilitate reading comprehension, a conducive classroom environment, the availability of adequate textbooks, and the role of supporting facilities such as libraries and digital media. Meanwhile, inhibiting factors include students’ infrequent exposure to Arabic texts outside class hours, difficulties arising from limited vocabulary mastery, psychological barriers such as anxiety, fear of making mistakes, and haste while reading, as well as limited access to dictionaries or other supporting media that could assist students in comprehending Arabic descriptive texts.